Studi Criminal Profiling pelaku penganiayaan berat (Studi di rumah tahanan kelas II B Raba Bima) - Fadillah, muhamadfadillah; Ufran; Amin, Idi (Parhesia, 2024)
This study is aimed at analyzing criminal profiling on perpetrators of serious assaults and to gain an understanding of the criminal acts that will occur by employing criminal profiling studies. The study used empirical legal research. The findings showed that using a criminal profiling study, we could find out how the perpetrator of the crime of serious assault in Class II B Detention Center Raba Bima. In forecasting, the perpetrator would use three stages, namely pre-occurrence (Profiling Crime), at the time of the occurrence (Actualization Crime), and the possibility that will occur (Probability Crime), so that the forecasting process will be able to elucidate the possibility and potential of criminal acts that will be committed by the perpetrator of serious assault. Keywords: Criminal Profiling; Forecasting Serious Offenders.